Pengembangan Media Pembelajaran Berbasis Android dalam Pembelajaran Pendidikan Agama Islam di Sekolah Menengah Kejuruan - Wahyuningsih, Nurnajmi; Zurqoni, Zurqoni; Afandi, Nur Kholik (FENOMENA, 2024)
The education sector is currently entering an era of modernization, marked by numerous innovations in the learning process. One aspect of modernization in education is the emergence of various types of media used throughout the learning process. From the meeting mechanisms, lesson planning, to the learning materials—everything can now be facilitated by media and technology. This study aims to develop a series of Islamic Religious Education (PAI) learning applications for vocational schools, specifically at SMK Negeri 2 Sebulu. It focuses on the development of Android-based learning media for Islamic Religious Education in vocational high schools and evaluates its feasibility for use. The research method is based on product development using the Borg and Gall model. Data were collected through questionnaires, interviews, and observations. The data collected from the questionnaires were analyzed by converting the average score results into percentages. The main subjects in this study were 10th-grade students of SMK Negeri 2 Sebulu. The research findings, based on data validation results, show that media experts provided scores of 87% and 80%, both indicating that the media is feasible for use. Meanwhile, the material evaluation received a score of 86%, also indicating that the media is suitable for use in the Islamic Religious Education learning process.